2003
DOI: 10.1016/s0194-5998(03)00526-6
|View full text |Cite
|
Sign up to set email alerts
|

Triamcinolone acetonide aqueous nasal spray and fluticasone propionate are equally effective for relief of nasal symptoms in patients with seasonal allergic rhinitis

Abstract: Differences in molecular potency of intranasal steroids do not confer differences in efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…This finding is in line with a previous placebo-controlled, parallel-group study including 28 patients with pediatric AR who received OD triamcinolone acetonide aqueous nasal spray (220 µg), in which headache was the most frequently reported AE, occurring in 18% of patients [38]. Similarly, headache was also the most frequently reported AE in the Berger et al [22] study, which compared the safety and efficacy of triamcinolone acetonide and fluticasone propionate in 295 patients with spring SAR (6.8 and 4.1% in the triamcinolone acetonide and fluticasone propionate treatment groups, respectively). Even though headache was considered as a TEAE in this study, a strong connection between AR and the occurrence of migraine appears to exist.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This finding is in line with a previous placebo-controlled, parallel-group study including 28 patients with pediatric AR who received OD triamcinolone acetonide aqueous nasal spray (220 µg), in which headache was the most frequently reported AE, occurring in 18% of patients [38]. Similarly, headache was also the most frequently reported AE in the Berger et al [22] study, which compared the safety and efficacy of triamcinolone acetonide and fluticasone propionate in 295 patients with spring SAR (6.8 and 4.1% in the triamcinolone acetonide and fluticasone propionate treatment groups, respectively). Even though headache was considered as a TEAE in this study, a strong connection between AR and the occurrence of migraine appears to exist.…”
Section: Discussionsupporting
confidence: 88%
“…In a study by Berger et al [22] in 295 patients with symptomatic SAR, the mean ± SD change in the total nasal symptom score was equivalent between the study medications: –3.15 ± 0.19 with triamcinolone acetonide and –3.17 ± 0.18 with fluticasone propionate after 21 days of treatment. Similarly, Kaiser et al [21] found a mean change in the total symptom score of –4.84 with triamcinolone acetonide and –4.81 with fluticasone propionate in 150 patients with severe SAR who were treated for 3 weeks.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Meltzer et al [26] found that once-daily fexofenadine hydrochloride (an antihistamine) in patients with seasonal allergic rhinitis led to significantly greater reductions in overall work impairment and in daily activity impairment compared with placebo (as measured by the Work Productivity and Activity Impairment instrument); overall RQLQ score was also significantly reduced (p < 0.01). In a separate study the use of two intranasal corticosteroid sprays (triamcinolone acetonide and fluticasone propionate) was compared [27]. The preparations were equally effective in improving health-related QoL; scores on the RQLQ were 2.3-4.4 at baseline compared with 1.1-2.2 at endpoint (p < 0.001 vs. baseline).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly (P≤0.05) less effective than beclomethasone in reducing sneezing [113] Equally efficacious as intranasal beclomethasone in reducing total eye symptoms [113] Equivalent to fluticasone propionate in improving TNSS [114] Equivalent to fluticasone propionate in improving ocular itching/tearing/redness [114] Equivalent to fluticasone propionate in improving TNSS [115] Equivalent to fluticasone propionate in improving RQLQ eye symptoms [115] P=0.001 vs oral loratadine in TNSS [116] Comparable efficacy to oral loratadine in reducing ocular symptoms [116] Ciclesonide Ib NA RCTs P≤0.01 vs placebo in rTNSS [117] Ocular outcomes not reported [117] P<0.001 vs placebo in rTNSS [118] Ocular outcomes not reported [118] P≤0.04 vs placebo in rTNSS [119] Ocular outcomes not reported [119] P<0.001 vs placebo in rTNSS [120] P<0.05 in RQLQ non-nose/eye symptoms [120] P<0.001 vs placebo in rTNSS [121] No significant improvement vs placebo in RQLQ eye symptoms [120] Oral medications Antihistamines (eg, desloratadine, bilastine, fexofenadine, levocetirizine)…”
Section: Rctsmentioning
confidence: 99%